2014
DOI: 10.1016/j.rboe.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nonspecific lumbar pain and associated factors among adolescents in Uruguaiana, state of Rio Grande do Sul

Abstract: ObjectiveTo identify the prevalence of nonspecific lumbar pain and associated factors among adolescents in Uruguaiana, state of Rio Grande do Sul.MethodsThis was a cross-sectional school-based study conducted among adolescents aged 10–17 years who were enrolled in the day shift of the municipal and state educational systems of Uruguaiana. This study evaluated 1455 adolescents. The data-gathering procedures involved two stages. Firstly, a questionnaire on sociodemographic indicators, behavioral patterns and hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…This result was in agreement with [36,43] they revealed that back pain was not significant associated with age of children and adolescents. On the contrary, other studies by [6,7,44] showed a significant association between age and frequency of occurrence of back pain in which a significant increase in prevalence as age increases. This difference may be related to variation in age group.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…This result was in agreement with [36,43] they revealed that back pain was not significant associated with age of children and adolescents. On the contrary, other studies by [6,7,44] showed a significant association between age and frequency of occurrence of back pain in which a significant increase in prevalence as age increases. This difference may be related to variation in age group.…”
Section: Discussionmentioning
confidence: 71%
“…Similarly to the result of [28] who stated that over half of students remain in a sitting position at least 8 hours per day in a sedentary activity, making it a risk factor for the occurrence of back pain. In contrast, a study conducted among adolescents aged 10-17 years by [44] who showed that the time spent doing sedentary activities did not present any relationship with lumbar pain. This difference may be related to various amounts of time spent in sedentary activities in other studies.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Hypermobility of such joints generates joint instability and consequent overload on stabilizing ligaments and muscles which, associated to increased weight, determine musculoskeletal system overload, pull the spine anteriorly and determine low back pain 1,3,4 . In non-pregnant women, lumbo-pelvic instability is a relevant factor for the genesis of low back pain, because musculoskeletal system unbalance leads to lack of dynamic stability and consequent overload of musculoskeletal structures 5 . Abdominal muscles are major stabilizers so the weaker these muscles, the more severe will be the joint instability and consequently more severe low back pain 5,6 .…”
Section: Introductionmentioning
confidence: 99%